ACCURACY OF CARDIOVASCULAR RISK ASSESSMENT MODELS ACROSS THE LIFE COURSE. (11th November 2018) - Dalton, J; Rothberg, M; Dawson, N; Zidar, D; Gunzler, D; NEOCARE, T; Perzynski, A
Abstract: Screening for risk of atherosclerotic cardiovascular disease (ASCVD)-related events (stroke, myocardial infarction, cardiovascular death) is an important recent development in cardiovascular prevention. Practice guidelines established by the American College of Cardiology and American Heart Association (ACC/AHA) now recommend tailoring cholesterol- and blood pressure-lowering therapies according to estimated ASCVD event risk based on the ACC/AHA Pooled Cohort Equations Risk Model (PCERM). The goal of this work was to evaluate the predictive accuracy of the PCERM among older patients. We analyzed data from 98, 248 Cleveland Clinic patients of white or black race with an outpatient lipid panel drawn between 2007 and 2010 (73, 561 aged 35–64 years at baseline; 19, 581 aged 65–79 years; and 5, 106 aged ≥80 years). Our analysis found that median [quartiles] of PCERM-predicted ASCVD event risk for the three age categories were 1.1% [0.4%, 2.7%], 7.8% [4.6%, 12.1%], and 21.7% [15.9%, 30.0%], respectively. Concordance statistics [95% confidence intervals] for the three age categories were 0.74 [0.73, 0.75], 0.64 [0.63, 0.66], and 0.55 [0.53, 0.57], respectively. Among those ≥80 years old, calibration plots indicated near independence of PCERM estimated 5-year ASCVD event probability from observed incidences. Our study suggests that risk-based cardiovascular prevention should be considered separately for older patients.